A report on the occlusal dental caries experience in deciduous, mixed and permanent dentition of school children in Chennai, Tamil Nadu 2017-18 - Anu, V.; Pavani, Bellamkonda; Judyangel, D.; Mayma, Natasha; Jyosthna, A. (International Journal Of Community Medicine And Public Health, 2020)
Background: Dental caries is the most common disease among the spectrum of oral diseases and is still a major public health burden in developing countries, affecting 60-90% of school children. To obtain a database about the dental caries prevalence among the school children in Chennai city, 2017-2018. Methods: A cross-sectional study was carried out among 2300 school children aged between 3 to 17 years in Chennai, Tamil Nadu. Dental caries was recorded using World Health Organisation (WHO) criteria of decayed, missing, and filled teeth (DMFT) and DMFT indices. Chi square test was done to assess the comparison between primary and mixed and mixed and permanent. DMFT and DMFT indices had extreme values, hence ‘0’ was set as median value and median test was applied. Results: The present study showed a higher prevalence of dental caries in primary (40.17%), mixed (‘d’ 33.02% and ‘D’ 38.8%) and permanent dentition (51.06%). The filled component is less with 0.85% in primary, 2.20% in mixed ‘f’, 0.58% in mixed ‘F’, and 2.98% in permanent dentition. The mean ‘DMFT’ in primary dentition is 1.32, mixed dentition mean ‘DMFT’ is 0.84, mixed dentition mean ‘DMFT’ is 0.96 and in permanent dentition mean DMFT is 1.57. Dental caries prevalence was found to be significantly more in males when compared to females. Conclusions: There is a higher prevalence of dental caries among school children in all three groups and this data can be used to plan preventive programmes to improve the oral health of this children.